Modeling and Reviewing Analysis of the COVID-19 Epidemic in Algeria with Diagnostic Shadow (CSIAM Transactions on Applied Mathematics, 2022)
In this paper, we formulate a special epidemic dynamic model to describethe transmission of COVID-19 in Algeria. We derive the threshold parameter control reproduction number $(\mathcal{R}^0_c),$ and present the effective control reproduction number $(\mathcal{R}_c(t))$ as a real-time index for evaluating the epidemic under different control strategies. Due to the limitation of the reported data, we redefine the number of accumulative confirmed cases with diagnostic shadow and then use the processed data to dothe optimal numerical simulations. According to the control measures, we divide thewhole research period into six stages. And then the corresponding medical resourceestimations and the average effective control reproduction numbers for each stage aregiven. Meanwhile, we use the parameter values which are obtained from the optimalnumerical simulations to forecast the whole epidemic tendency under different controlstrategies.